Product Design And Development Using Virtual Reality And CAD/CAM System - Lee, Kai Chen (Universiti Sains Malaysia, 2022)
The complex product evaluation process can be costly and time-consuming throughout various stages of a design process. Therefore, the present project aims to develop a product towards I4.0 by integrating VR technologies and CAD/CAM systems into the PDD process to make possible improvements against the limitations while reducing the time and costs in the development cycle, ensuring its quality and usability. Throughout the screening and scoring processes, a wrist rehabilitation device is selected as a potential product for further development using VR technology. In expectation, the device has a lower production cost and a simpler working mechanism for fulfilling the requirements of the patients. Hence, the spring feature in the proposed concept AC is replaced with a resistance band for providing various semiautomatic wrist motions in 3-DOF. On top of that, a 3D CAD model of the device is created using SOLIDWORKS 2021 and the visualization of its assembly model and animation in a VR environment is carried out with the EpicCADVR application using Oculus Quest 2 VR device. Thus, the continuous PDD process can be much simpler as it allows the users to examine and verify the initial design of parts virtually for further necessary modification. Also, the demonstration of device usage in FPV instructs the wrist mechanism and encourages the patients to move their wrists through an appropriate ROM, emulating the movement therapy. Eventually, the final device product has been constructed by combining the 3D-printed parts with some standard parts acquired, possessing an approximate weight of 600.66 g. Testing of the product has proven the operating performance of 3-DOF wrist motions, such as flexion/extension, pronation/supination, and abduction/adduction. From the analysis, the achieved ROM exceeds the minimum ROM required to perform ADL. Finally, the total estimated production cost of the final product is RM 121.41, which is comparatively lower than other benchmarking products. The device developed in this study demonstrates the potential for utilizing VR technology in the PDD phase with its immersive experience in FPV. Thus, further implementation of VR systems in PDD has been recommended to explore its possibilities against the limitations. Work undertaken in this project represents a significant step towards the realization of the final product with the aid of a VR system.